Perception towards Mental Illness in Southern Tamil Nadu: A Cross Sectional Study - Krishnaleela G; Siva PM; Jose, Christina Mary; Kabilan, Deepak; Chitra P; Dharsini G V; Dhivyabharathi SB (National Journal of Community Medicine, 2019)
Background: Psychiatric disorders are widely considered as a major contributor to the global burden of diseases worldwide. Psychiatric patients are subjected to cultural stereotypes and negative attitude by general population. This study aims to assess the perception towards mental illness among people of Mukkudal, Tirunelveli district, Tamil Nadu. Methods: This is a cross-sectional survey conducted among 250 people aged above 18 years residing in Mukkudal village of Tirunelveli district, Tamil Nadu. Questionnaire including basic demographic information, BMI scale was used to assess the perception among general population. Results: Out of 21 questions people were found to have poor perception towards 10 questions (>50%).72% of people were found to believe that it is embarrassing to have a mentally ill person in their family.People belonging to the age group 40- 50; female by sex; Christian by religion; positive family history for mental illness; socio-economic class were found to have poor perception towards mental illness. Conclusions: Creating awareness using film stars and Celebrities may help to improve the perception among lower socio economic classes. Strategies to increase social contact of public with people having mental illness could be considered in the implementation of anti- stigma programs.